Efficiency of some control agents against nosema disease (Nosema apis zander) infecting honeybee colonies (Apis mellifera l.) - Yousif, Khalil, S.I; EI-Shakaal, S.M.A.; Abou-Lila, S.M.; Abd-Alla, M.A. (2007)
A detailed study was carried to evaluate the efficiency of metronidazole, wormwood (Artimisia cinae Willkomm) and wormwood + thyme (Thymuo vulgaris L.) extracts (1: 1 wtlwt), offered in sugar syrup, in repressing the development of Nosema disease infecting honeybee colonies during two period February 2002 and 2003. The subsequent effects on worker brood rearing activity, development of workers body weight and honey production of treated colonies were also studied.
Includes reference.
Summary in Arabic.
1
Keywords: Honeybee -- Diseases -- Egypt; Nosema apis; Bee culture; Wormwood; Thymes; Plant extracts